Atlas of human infectious diseases - Horby, Peter; Wertheim, Heiman F. L.; Woodall, John P. (Wiley-Blackwell, 2012)
The Atlas of Human Infectious Diseases provides a much needed practical and visual overview of the current distribution and determinants of major infectious diseases of humans. The comprehensive full-color maps show at a glance the areas with reported infections and outbreaks, and are accompanied by a concise summary of key information on the infectious agent and its clinical and epidemiological characteristics. Since infectious diseases are dynamic, the maps are presented in the context of a changing world, and how these changes are influencing the geographical distribution on human infections. This unique atlas : Contains more than 145 high quality full-color maps covering all major human infectious diseases; Provides key information on the illustrated infectious diseases; Has been compiled and reviewed by an editorial board of infectious disease experts from around the world. The result is a concise atlas with a consistent format throughout, where material essential for understanding the global spatial distribution of infectious diseases has been thoughtfully assembled by international experts. Atlas of Human Infectious Diseases is an essential tool for infectious disease specialists, medical microbiologists, virologists, travel medicine specialists, and public health professionals. The Atlas of Human Infectious Diseases is accompanied by a free enhanced Wiley Desktop Edition -- an interactive digital version of the book with downloadable images and text, highlighting and note-taking facilities, book-marking, cross-referencing, in-text searching, and linking to references and glossary terms